Hubungan Status Gizi Dan Asupan Gizi Ibu HamilTrimester Iii Dengan Panjang Bayi LahirDi Puskesmas Bendosari Kabupaten Sukoharjo - Syafaah, Hanissa, Muwakhidah, SKM., M.Kes, Dwi Sarbini, S.ST., M.Kes (2016)
Introduction : Infant birth length is one of the indicators to evaluate the acquirement fetal needs during pregnancy. Nutritional status and maternal intake of pregnant women have an impact on the fetal growth during the pregnancy. This may affect on infant birth size especially on birth length. Objective : The aim of the study was to determine the association between nutritional status and maternal intake of third trimester pregnancy with infant birth length at Puskesmas Bendosari, Sukoharjo. Research Methods : This study was an observational analitic research with cross sectional design. The population was all of the pregnant women in the third trimester at Puskesmas Bendosari. Subjets were 36 third trimester pregnant women that comply the inclusive and eksclusive criterias and were selected by consecutive sampling method. MUAC (Mid Upper Arm Circumference) was measured with MUAC tape and hemoglobin level was measured by hemocue. Maternal intakes were measured with Semi-Quantitative Food Frequency Quesioner (SQ-FFQ). Infant birth length was obtained by checking the birth record. Data analysis was done by correlation test (Pearson Product Moment test) and single linier regression method. Results : The average of MUAC was 26,73±2,39 cm and hemoglobin level was 10,70±1,13 g/dl. The average of maternal intake of energy, protein, and iron were 2103,05±264,33 Kkal, 72,95±16,45 gr, and 28,69±7,11 mg; respectively, the average of infant birth length was 47,88±2,17 cm. Factors associated to infant birth length were energy intake (p=0,000, r=0,450), protein intake (p=0,001, r=0,302), and iron intake (p=0,000, r=0,567). The linier regresion showed that iron intake of pregnant women was the determinant factor of infant birth length (56,7%). Conclusion: Maternal intake of energy, protein and iron were associated to infant birth length.